TREMATODOS DE LAS RANAS DE LA CIENAGA DE LERMA MEXICO I - CABALLERO Y C, EDUARDO; C, EDUARDO (San Antonio Rancho, GUADALAJARA, JALISCO, MEX, 1942)
The authors describe P naevius as a parasite of frogs of the banana plantations in the zone of Cordoba, Ver Mexico
ANS INST BIOL
Keywords: TREMATODOS, RANAS, CIENAGA DE LERMA, MEXICO I; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; COMPORTAMIENTO ANIMAL